Explanatory Factors Associated With ICT Integration In Teaching Secondary School Agriculture: Case Of Southern Africa (Swaziland) - Mndzebele, Nomsa M.; Dludlu, Mzomba Nelson (Advances in Social Sciences Research Journal, 2018)
As ICT continues to make head way in the Western countries, the African countries are lagging behind and this widens the gap in respect of North–South digital divide. The focus of this paper is factors associated with integration of ICT in the teaching of secondary school agriculture. This is a case study of Swaziland, a country in Southern Africa. The study adopted a descriptive survey research design. Population of study was a census of secondary agriculture teachers and employed a survey questionnaire. Data analysis employed descriptive statistics and regression. Findings established that teachers do occasionally use ICT tools in instructional delivery. Factors influencing ICT integration: 1) Digital proficiency in using ICT tools, 2) Social influence, 3) Sharing digital content with learners,4) Possession of personal computer, and 5) Internet connectivity. It was recommended that teacher pre-service education should prioritize integration of ICT in the teacher preparation programme. School administrators should buy into Internet connectivity for their schools.